Revisiting the demand and profitability of chemical fertilizers amid global fuel-food-fertilizer crisis: Evidence from Ethiopia - Assefa, Thomas; Berhane, Guush; Abate, Gashaw T.; Abay, Kibrom A. (International Food Policy Research Institute, 2024)
We revisit the state of smallholder fertilizer demand and profitability in Ethiopia in the face of the recent global fuel–food–fertilizer price crisis triggered by the Russian–Ukraine war and compounded by other domestic supply shocks. We first examine farmers’ response to changes in both fertilizer and food prices by estimating price elasticity of demand. We then revisit the profitability of fertilizer by computing average value–cost ratios (AVCRs) associated with fertilizer application before and after these crises. We use three-round detailed longitudinal household survey data, covering both pre-crisis (2016 and 2019) and post-crisis (2023) production periods, focusing on three main staple crops in Ethiopia (maize, teff, and wheat). Our analysis shows that fertilizer adoption, use, and yield levels were increasing until the recent crises, but these trends seem halted by these crises. We also find relatively large fertilizer price elasticity of demand estimates, ranging between 0.4 and 1.1, which vary across crops and are substantially larger than previous estimates. We find suggestive evidence that households with smaller farm sizes are relatively more responsive to changes in fertilizer prices. We also document that farmers’ response to increases in staple crop prices is not as strong as perceived and hence appears to be statistically insignificant. Finally, we show important dynamics in the profitability of chemical fertilizer. While the AVCRs show profitable trends for most crops, the share of farmers with profitable AVCRs declined following the fertilizer price surge. Our findings offer important insights for policy focusing on mitigating the adverse effects of fertilizer price shocks.